The Thirst for Religion in the Modern World and Islamic View point amongst the World Religions = Hajatu al-Insan Ila al-din - Khan, Musaddiq Majid; Khan, Israr Ahamd (Sheikh Zayed Islamic Centre, University of the Punjab New Campus, Lahore-54590 Pakistan, 2013)
Religion is the core component of human life. The focal point of Quranic guidance is to explain what is religion? Some scholars are of the view that in the lives. They consider the religion something supernatural. They did not accept that there are some natural rules working in the cosmos. Some other scholars consider it merely according to the human nature and universal cause and effect relationship. They claim that religion in its very being is in total accordance to that of nature. This principle inclines human beings to live under the influence of their instinct and in consequence they find no way to abide by the eternal principles of religion. In this article attempt has been made to discover true placement of religion and nature in the light of the holy Qur'an.